Impact of Gastric H+/K+-ATPase rs2733743 on the Intragastric pH-Values of Dexlansoprazole Injection in Chinese Subjects - Sun, Lu-Ning; Cao, Yang; Li, Yue-Qi; Fang, Yun-Qian; Zhang, Hong-Wen; Wang, Mei-Feng; Xie, Li-Jun; Chen, Juan; Yang, Zhi-Cheng; Bian, Ming-Liang; Li, Hao; Zhang, Pei-Pei; et al. (Frontiers in Pharmacology, 2017)
Background: Not all patients with acid-related disorders receiving proton pump inhibitor treatment get adequate gastric pH control. The genetic variation of receptors, metabolic enzymes and transporters are known to cause failures of therapies. We have conducted a study to evaluate the influence of gastric H+/K+-ATPase, CYP2C19 and ABCB1 polymorphisms on the pharmacokinetic and pharmacodynamic profiles of dexlansoprazole injection in healthy Chinese subjects. Methods: A total of 51 subjects were enrolled for pharmacokinetic and pharmacodynamic study after a single intravenous administration of 20 or 30 mg dexlansoprazole. Plasma concentrations were determined using a chiral liquid chromatography-mass spectrometry method. The intragastric pH and baseline-adjusted intragastric pH parameters were introduced to evaluate the pharmacodynamic characters. Genotyping was performed by polymerase chain reaction. Results: The pharmacokinetic parameters were significantly influenced by CYP2C19 phenotypes, and gastric acid secretion inhibition were affected by both gastric H+/K+-ATPase and CYP2C19 polymorphisms. Gastric H+/K+-ATPase genotypes had greater effects than CYP2C19 genotypes on the suppression of gastric acid secretion. Conclusion: Gastric H+/K+-ATPase polymorphism may be one of the main reasons that cause insufficient gastric acid inhibition.